What Is Being Learned About Starch Properties from Multiple‐Level Characterization. Issue 4 (30th July 2013) - Gilbert, Robert G.; Witt, Torsten; Hasjim, Jovin
ABSTRACT: A survey is given of methods to characterize the lowest three levels of starch structural features: individual chains, branched molecules, and the arrangement of branched molecules in a sample (e.g., crystalline and amorphous lamellae of starch granules in grain). The survey also covers ways of treating the results so as to understand starch structure–property correlations: for example, the structural characteristics that control the rate of digestion of a starch‐containing food. A number of studies are then examined not only to show how these techniques have been used to discover correlations between these structural characteristics and properties of importance but also to deduce reasonable causal explanations for the correlations. An overview of problems that have not yet been solved in each of these starch structural levels is also given. The applications of these characterization methods have considerable potential as tools to choose and process native starches with improved functional properties for human food, animal feed, and industrial uses, including biomaterials.